Relationship between Burnout Syndrome Symptoms and Demographic Characteristics among Long-Term COVID-19 Hospital Healthcare Workers in South Sumatra, Indonesia - Artanto, Ardi; NurAnggina, Dientyah; Ghiffari, Ahmad; Huda, Dimas Farizul; Ilma, Ridha (International Journal of Human and Health Sciences (IJHHS), 2023)
Background: During the COVID-19 pandemic, the workload of health professionals grew significantly, particularly in the service sector. Such heavy workload, particularly for those working on the front lines, can result to burnout syndrome. Objective: To find the correlation between long-term COVID-19 service personnel characteristics and burnout syndrome symptoms at hospitals. Methods: This cross-sectional, analytic study was done on health workers that managed COVID-19 at Palembang Muhammadiyah Hospital and Palembang BARI Hospital in South Sumatra, Indonesia. Purposive sampling was used to sample, with 88 samples total that satisfied the inclusion and exclusion criteria. A questionnaire was filled out to collect the data. Results: Based on the research results of data sets, there was a correlation between age and burnout syndrome (p=0.000), sex and burnout syndrome (p=0.006), COVID-19 service period and burnout syndrome (p=0.002), working hours per day and burnout syndrome (p=0.014), and marital status and burnout syndrome (p=0.013). Conclusion: Long-term COVID-19 service personnel and burnout syndrome symptoms in those hospitals are directly interrelated. International Journal of Human and Health Sciences Vol. 07 No. 02 Apr’23 Page: 117-121